Distinct responses of wheat microbial communities in phyllosphere and rhizosphere to Puccinia striiformis infection - Gao, Feng; Ma, Liya; Chen, Xiao; Xue, Xin; Hou, Junhong; Dong, Junhong; Shen, Weimin; Yang, Chunling; Shi, Yu (Frontiers in Microbiology, 2025)
In the plant ecosystem, microbiomes are of great significance in sustaining plant health, participating in multiple physiological activities like nutrient metabolism, stress resistance, and hormone regulation. However, the invasion of pathogens like Puccinia striiformis can disrupt the balance of the plant microbiome, significantly affecting plant growth, development, and metabolism. This study delved into the responses of wheat microbial communities in different niches, namely the phyllosphere and rhizosphere, to P. striiformis infection. The structure of the phyllosphere fungal community was predominantly affected by the wheat variety. The α–diversity of phyllosphere fungi increased with the enhancement of wheat resistance. In the rhizosphere, although the inoculation did not cause a notable alteration to the overall architecture of the bacterial and fungal communities, remarkable variations were detected in the relative proportion of certain microbial taxa across various resistant wheat varieties. The co-occurrence network of the rhizosphere underwent significant structural and functional reorganization, and the network became substantially more complex after inoculation. The study also uncovered the interaction among the microbial communities in the phyllosphere and rhizosphere, with highly resistant varieties showing a stronger ability to coordinate this interaction to optimize microbial community functions and enhance disease resistance. This research deepens the understanding of the wheat—Puccinia striiformis—microbial community interaction system and paves the way for further research on wheat disease prevention and control strategies.